Nature's wrath ; Home in Berlin ; Golden opportunity [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Probe looks into illegal logging as one of the main causes of destruction in Ormoc, Leyte; interviews with two Filipino jazz musicians about their life in Berlin and the atmosphere it provides their music; prospects of our country in the upcoming Games in December, 1991.